A Case Study of Technology Leadership in Situ: A High School iPad Learning Initiative. Issue 2 (March 2016) - Hughes, Joan E.; Boklage, Audrey; Ok, Min Wook
This research examined how technology leadership functioned in the first year of a tablet computer (iPad) learning innovation in one U.S. high school and its district. This article presents a descriptive case study of leader interactions that contributed to setting direction, providing professional learning, and making the organization technologically ready. Qualitative data, collected through interviews and observations, revealed a "bottom-up" innovation with "top-down" support. Yet, the school's entrenched structural and cultural practices undermined attempts to enact the learning-focused vision. This study emphasizes the need for a truly distributed vision, in which all organizational structures, practices, policies, and expectations are reconsidered.